C. elegans whole-genome sequencing reveals mutational signatures related to carcinogens and DNA repair deficiency - Meier, Bettina; Cooke, Susanna L.; Weiss, Joerg; Bailly, Aymeric P.; Alexandrov, Ludmil B.; Marshall, John; Raine, Keiran; Maddison, Mark; Anderson, Elizabeth; Stratton, Michael R.; Gartner, Anton; Campbell, Peter J. (Genome Research, 2014)
Mutation is associated with developmental and hereditary disorders, aging, and cancer. While we understand some mutational processes operative in human disease, most remain mysterious. We used Caenorhabditis elegans whole-genome sequencing to model mutational signatures, analyzing 183 worm populations across 17 DNA repair-deficient backgrounds propagated for 20 generations or exposed to carcinogens. The baseline mutation rate in C. elegans was approximately one per genome per generation, not overtly altered across several DNA repair deficiencies over 20 generations. Telomere erosion led to complex chromosomal rearrangements initiated by breakage–fusion–bridge cycles and completed by simultaneously acquired, localized clusters of breakpoints. Aflatoxin B1 induced substitutions of guanines in a GpC context, as observed in aflatoxin-induced liver cancers. Mutational burden increased with impaired nucleotide excision repair. Cisplatin and mechlorethamine, DNA crosslinking agents, caused dose- and genotype-dependent signatures among indels, substitutions, and rearrangements. Strikingly, both agents induced clustered rearrangements resembling “chromoanasynthesis,” a replication-based mutational signature seen in constitutional genomic disorders, suggesting that interstrand crosslinks may play a pathogenic role in such events. Cisplatin mutagenicity was most pronounced in xpf-1 mutants, suggesting that this gene critically protects cells against platinum chemotherapy. Thus, experimental model systems combined with genome sequencing can recapture and mechanistically explain mutational signatures associated with human disease.